Bilateral sinonasal inverted papilloma: case report and literature review - Wong, Kim Yew Richard; Asha'ari, Zamzil Amin; Ahmad, Mohd Zaki; Abd Rahman, Azlina (Japan International Cultural Exchange Foundation, 2017)
Objective: To describe a rare case of bilateral sinonasal inverted papilloma and review the relevant literature. Design: Case report. Materials and Methods: Medical record review and literature search. Results: A 50-year-old gentleman presented with bilateral nasal polyposis involving posterior ethmoid and sphenoid sinuses. With clinical diagnosis of benign inflammatory polyposis, he underwent bilateral functional endoscopic sinus surgery. The histopathological examination revealed the diagnosis of bilateral inverted papilloma. He remains disease free after 5 years follow up. A literature review on the subject is presented. Conclusion: This case highlighted the unique presentation of sinonasal inverted papilloma as a bilateral disease and in the posterior group of paranasal sinuses.